Atmosfera controlada dinâmica monitorada pelo quociente respiratório: efeito do manejo do etileno, temperatura e níveis de CO2 sobre compostos voláteis e conservação de maçãs - Both, Vanderlei (2015)
The decrease in oxygen levels during storage of apples in controlled atmosphere (CA) reduces ethylene production, respiration rate and delay fruit ripening. Excessively low O2 levels induce the fermentative pathway, producing fermentation compounds, if in excess, cause flesh breakdown and affect the aroma. Therefore, it is essential to monitor the minimum O2 threshold during storage, using a technique called dynamic controlled atmosphere (DCA). This thesis is composed of five papers, which resulted from studies with the following aims: to evaluate volatile compounds production in apples after storage in controlled atmosphere (CA) with extremely low O2 levels and DCA, and compare them with standard CA; to compare storage in conventional CA with the DCA by the chlorophyll fluorescence technique (DCA-CF) and respiratory quotient (DCA-RQ) with respect to fruit quality maintenance; to determine the optimum RQ level for the different apples cultivars and evaluate the effect of different temperature and CO2 levels during DCA storage on apple quality. Royal Gala , Galaxy and Fuji Kiku apples were stored for 9 months and plus 7 days of shelf life (20 °C) before the quality analyses. In general, the fruit quality maintenance, on basis of storage conditions occur in the following order: DCA-RQ > DCA-CF > standard CA. Despite the higher production of fermentative compounds in the higher RQ levels, there was no greater difference between the levels of RQ studied, although a trend towards better RQ 1.5 on Royal Gala apples. 1-Methylcyclopropene (1-MCP) application in Galaxy and Fuji Kiku apple stored in DCA-RQ does not improve quality, furthermore 1-MCP increases decay incidence in Fuji Kiku apples. The temperature of 2.0 ºC in storage of Galaxy apples in DCA-RQ, maintains better quality than lower temperatures used in standard CA, saving electrical energy with the refrigeration systems of the storage rooms. 1-MCP application in fruits stored in standard CA may be another strategy to increase storage temperature. CO2 levels, in DCA-RQ storage, can be kept at 1.4 kPa for Fuji Kiku apples and up to 1.6 kPa for Galaxy apples. The use of extremely low O2 levels (0.5 to 0.7 kPa) or DCA-RQ decreases some volatile compounds, especially straight chain esters, while other impact compounds of the aroma are not impaired in relation to standard CA storage. In DCA-CF volatile compounds production are sharply reduced in comparison to standard CA and DCA-RQ, probably due to the initial low oxygen stress, which occurs in DCA-CF.